2023
DOI: 10.3390/life13030754
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil Compounds of Andaliman (Zanthoxylum acanthopodium DC.) Fruit Varieties and Their Utilization as Skin Anti-Aging Using Molecular Docking

Abstract: Exposure to UV/infrared (IR) radiation is the main extrinsic factor that changes skin morphology and affects the increase in reactive oxygen species (ROS) in skin aging. Ten varieties of andaliman (Zanthoxylum acanthopodium DC.) fruit are presumed to have skin anti-aging compounds via an enzyme-inhibition mechanism. This study aims to compare ten essential oils (EOs) of andaliman fruit varieties, group them according to their varieties, and obtain the chemical components that can be used as potential skin anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…Then, the optimized ligands were also imported into the AutoDockTools software, version 1.5.7, to add polar hydrogens and Gasteiger charges. All ligands were kept exible before being saved in (.pdbqt) format (Hanwell et al 2012;Yan et al 2022;Kintamani et al 2023).…”
Section: Analysis Of Docking Molecularmentioning
confidence: 99%
“…Then, the optimized ligands were also imported into the AutoDockTools software, version 1.5.7, to add polar hydrogens and Gasteiger charges. All ligands were kept exible before being saved in (.pdbqt) format (Hanwell et al 2012;Yan et al 2022;Kintamani et al 2023).…”
Section: Analysis Of Docking Molecularmentioning
confidence: 99%
“…Similarly, molecular docking has been utilized in the selection of compounds present in ginger essential oil for their potential as anti-acne and antiskin aging agents, as demonstrated by Asoka et al (2022aAsoka et al ( , 2022b. In another study, Kintamani et al (2023) employed in silico methods to identify active compounds in andaliman essential oil with anti-skin aging properties. Furthermore, molecular docking and dynamics have been utilized by Nurlela et al (2022) to predict the efficacy of diterpenoid kaurene compounds as specific antiviral candidates against SARS-CoV-2.…”
Section: Receptorsmentioning
confidence: 99%
“…We have used this method before to reveal the potential of Andaliman (Zanthoxylum acanthopodium DC.) fruit essential oil as an anti-aging agent and antiacne potency of red ginger 30,31 . In this study, all identified components were further subjected to molecular docking study to confirm their potential to inhibit the skin-aging-related enzymes.…”
Section: Molecular Docking Studiesmentioning
confidence: 99%